Process Development for Bioactive Peptide Production - Gnasegaran, G.; Agyei, D.; Pan, S.; Sarethy, I.; Acquah, C.; Danquah, Michael (Springer Nature, 2017)
Bioactive peptides (BPs) are protein hydrolysates able to induce positive physiological responses when introduced into the body, making them useful ingredients in food, cosmetic and pharmaceutical products. However, the full potential of BPs has not been fully explored because research is still lacking on economical and scalable production methods. This study is therefore aimed at the development of a bioprocess for the production of novel bioactive peptides from food proteins by exploiting fermentative and the proteolytic activities of Lactobacillus delbrueckii subsp. lactis 313 (LDL 313). The optimum parameters and conditions for the production of antihypertensive peptides using LDL 313 were obtained from the literature and covered the upstream, midstream and downstream stages. The feasibility of manufacturing BPs in a large scale was also projected by conducting an economic assessment and a quantitative analysis based on the medical needs of hypertensive patients in Malaysia. Results indicated that to meet the needs of the hypertensive population, a production level of 1.267 kg milk protein/kg peptide had to be obtained at an enzyme requirement of 0.2 kg enzyme/kg milk protein. At this production level and at a peptide market value of USD 88.5/g peptide, the annual expected value of peptide will be USD 41,858,307,460. It will take about 19.5 h to produce one batch of the peptides at a total annual cost (equipment and utilities) of USD 15,081,885. An annual revenue of USD 42 billion is therefore expected from the entire bioprocess implying that the process is economically feasible.